Sensitive Mechanism and Instability Modeling Methods of Flexible Sensing Films Based on 2D Materials - Guishan Wang; Can Yang; Bowen Liu; Xinlei Zou; Chengguo Yu (Crystals, 2025)
This paper examines sensing mechanisms and stability issues of flexible sensors used in morphing wing applications. A key challenge is the lack of theoretical frameworks that accurately predict sensor behavior during complex deformation. Current models struggle to fully capture the relationships between mechanical strain, electrical response, and material properties. We first analyze the microscopic mechanisms and macroscopic sensing characteristics of 2D material-based sensitive films, developing strain-sensitive models based on crack effects and pressure-sensitive models based on slip effects. Through power spectrum analysis, we establish a quantitative model linking microscopic cracks to macroscopic electrical properties. Using this model, we study the factors affecting flexible sensing stability and propose a quantitative description model using dual-layer multi-channel flexible sensors. After simulation validation, our model successfully guides the structural design of flexible sensing films, offering a clear approach to improve flexible sensor stability.